(3GdJbhje aj GdJQHjI GdQjGVjI Hjf GdJMhdGJ GdQbejI heSQYGJ GdCfLGR GdQjGVjs - (3ZGRj(B, (3eMeO YGUes ((3YeGfs (3GdhQGb ddfTQ h GdJhRjYs, 2022)
(3jSJYQV gPG GdcJGH OhQ GdJbhje aj GdJQHjI GdQjGVjI aj Xd GdJMhdGJ GdQbejI GdeJSGQYI, eY GdJQcjR Ydi CgejI GdJbhje aj JMbjb GdCgOGa GdefThOI aj VhA GdQDjI GdYGdejI ddJYdje dYGe (B2030. (3jbOe GdcJGH JMdjdkG YejbkG dCMOK GdJbfjGJ GdeSJNOeI aj eLGd GdJbhje GdQjGVj, hcja jecf dgPg GdJbfjGJ Cf JSGge aj JWhjQ COGA GdQjGVjjf hJMbjb GdCgOGa GdefThOI(B.s
Keywords: (3GdJQHjI GdQjGVjI (B- (3GdJbhjes